472. The Utility of Infectious Diseases E-consults in the Era of COVID-19. (31st December 2020) - Saad, Hala; Yagnik, Kruti; King, Helen; Bedimo, Roger; Medford, Richard J
Abstract: Background: During the COVID-19 pandemic, rapid Infectious Diseases (ID) consultation has been required to answer novel questions regarding SARS-CoV-2 testing and infection prevention. We sought to evaluate the utility of e-consults to triage and provide rapid ID recommendations to providers. Methods: We performed a retrospective study reviewing ID e-consults in three institutions in the North Texas region: Clements University Hospital (CUH), Parkland Hospital and Health System (PHHS), and the VA North Texas Health Care System (VA) from March 1, 2020 to May 15, 2020. Variables collected include age, sex, ethnicity, comorbidities, time to completion, reason for consult and outcome of consult (initiation or removal of personal protective equipment (PPE) and recommendation to test or retest for COVID-19). Results: We performed all analysis using R studio (Version 1.3.959). Characteristics of 198 patients included: 112(57%) male, 86(43%) female, 86(43%) Caucasian, 71(36%) Hispanic, 42(21%) African American, 6(3%) Asian and mean(sd) age of 55.1(15.9). Patient comorbidities included: 89(45%) with a heart condition, 77(39%) diabetes, 30(15%) asthma and 14(7%) liver disease. Median time to completion for all hospitals was 4 hours(h); ((CUH (4h) vs PHHS (2h), p< 0.05; VA (5.5h) vs PHHS (2h) p< 0.05)). Most common reasons for e-consult included: (63)32% regarding re-testing ((CUH 14(21%) vs PHHS 43(50%), p< 0.05; CUH vs VA 14(27%), p< 0.05; PHHS vs VA, p< 0.05)), (61)31% testing ((CUH 25(37%) vs PHHS 39(45%), p< 0.05; CUH vs VA 7(16%), p< 0.05; PHHS vs VA, p< 0.05)) and 61(31%) infection prevention (IP). Based on the e-consult recommendation, 53(27%) of patients were tested ((CUH 31(45%) vs PHHS 11(13%), p< 0.05, CUH vs VA 11(25%), PHHS vs VA, p< 0.05)), 45(23%) were re-tested, 44(22%) of patients had PPE started on and 19% had PPE removed ((CUH 0(0%) vs PHHS 16(19%), p< 0.05; CUH vs VA 21(48%), p< 0.05; PHHS vs VA, p< 0.05)). Reason for Consult Conclusion: E-consult services can provide prompt ID input during the COVID-19 pandemic, minimizing the risk of infection to the patient and health care workers while preserving PPE and testing supplies. Disclosures: Roger Bedimo, MD, MS, Gilead Sciences (Consultant)Merck & Co. (Advisor or Review Panel member)ViiV Healthcare (Advisor or Review Panel member, Research Grant or Support)